2001
DOI: 10.1002/pds.574
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study of adverse events monitored by hospital pharmacists

Abstract: Pharmacist-led monitoring in a typical NHS hospital setting was effective at detecting ADRs in newly marketed drugs. However, this effort might have been substantially less time-consuming and more effective were electronic patient records (EPRs) available. Pharmacy computer systems are not designed to be patient focused and are therefore unable to identify patients taking newly marketed drugs. It is argued that future EPR and computerised patient-specific prescribing systems should be designed to capture this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Hospital pharmacists had more favourable attitudes than community pharmacists as they may be more knowledgeable about clinical pharmacy and pharmacovigilance, have access to patient medical records and tend to see more patients with serious ADEs [53–56]. In addition, hospital pharmacists are more directly involved in patient care, and have access to state of the art computer systems which may not be available in the community setting [57, 58]. These factors increase their chances of detecting serious ADEs compared with community pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital pharmacists had more favourable attitudes than community pharmacists as they may be more knowledgeable about clinical pharmacy and pharmacovigilance, have access to patient medical records and tend to see more patients with serious ADEs [53–56]. In addition, hospital pharmacists are more directly involved in patient care, and have access to state of the art computer systems which may not be available in the community setting [57, 58]. These factors increase their chances of detecting serious ADEs compared with community pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that shows that the pharmacist is both willing and capable to adequately fulfil the role of a reporter of ADRs. [25][26][27][38][39][40][41] In addition to this direct role, the pharmacist can also play a coordinating role, both in general practice and in a hospital setting. The fact that in many countries most Table 2.…”
Section: Differences Per Member Statementioning
confidence: 99%
“…Hospital led monitoring systems to report and identify ADRs can also be used along with other spontaneous reporting systems for better monitoring of ADRs as it will provide better understanding of events related to ADR [8]. A study from the UK reported, that although hospital pharmacists were well aware of ADR reporting schemes, were inconsistent in reporting [23].…”
Section: Adr Monitoring Trends In Developed Countriesmentioning
confidence: 99%
“…Pharmacist-led monitoring system at the hospital is effective in detecting ADRs of newly marketed drugs. However, only computer programs not designed as patient focused is not able to identify patients taking newly marketed drugs which should be under strict surveillance [8]. The pharmacist has helped to improve outcomes including reduction in ADRs and medication errors by improving medication adherence through counseling and telephone follow-up which has resulted in identification of preventable adverse drug events.…”
Section: Introductionmentioning
confidence: 99%